2021
DOI: 10.1007/s11739-021-02669-0
|View full text |Cite
|
Sign up to set email alerts
|

Emergency room comprehensive assessment of demographic, radiological, laboratory and clinical data of patients with COVID-19: determination of its prognostic value for in-hospital mortality

Abstract: Mortality risk in COVID-19 patients is determined by several factors. The aim of our study was to adopt an integrated approach based on clinical, laboratory and chest x-ray (CXR) findings collected at the patient’s admission to Emergency Room (ER) to identify prognostic factors. Retrospective study on 346 consecutive patients admitted to the ER of two North-Western Italy hospitals between March 9 and April 10, 2020 with clinical suspicion of COVID-19 confirmed by reverse transcriptase-polymerase reaction chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
1
8
1
Order By: Relevance
“…In addition, He et al found that patients had derangements in coagulation profile studies at the time of presentation [ 25 ]. However, not all laboratory findings were normal in our study; elevated levels of CRP and ferritin were noted in the initial measurements taken in the ED for the majority of our patients, which could be explained by the fact that the levels of these inflammatory markers could be influenced by disease activity early in the course of the disease, as mentioned by a few other papers [ 5 , 21 , 26 ].…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…In addition, He et al found that patients had derangements in coagulation profile studies at the time of presentation [ 25 ]. However, not all laboratory findings were normal in our study; elevated levels of CRP and ferritin were noted in the initial measurements taken in the ED for the majority of our patients, which could be explained by the fact that the levels of these inflammatory markers could be influenced by disease activity early in the course of the disease, as mentioned by a few other papers [ 5 , 21 , 26 ].…”
Section: Discussioncontrasting
confidence: 65%
“…However, some patients may present with non-specific symptoms, such as headache and dizziness [ 4 ]. Recent studies have shown that elderly patients with multiple comorbidities and high levels of inflammatory markers usually have a higher mortality risk than others [ 5 , 6 ]. A recent study published in March 2021 showed that male sex, lymphopenia, elevated C-reactive protein (CRP), and presence of comorbidities are all potential risk factors for poor outcomes in COVID-19 patients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are many significant factors that can play a major role in predicting COVID-19 outcomes, including sex, age, and clinical and laboratory findings [ 8 - 9 ]. In addition, comorbidities such as hypertension, diabetes mellitus, and asthma were among the strongest predictors of COVID-19 outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Balbi [ 43 ], d’Souza [ 44 ] and Au-Yong [ 45 ] correlated the Brixia A score with outcomes in COVID-19 patients. Setiawati [ 46 ] found that severe cases of COVID-19 pneumonia had a Brixia score over 6, Gatti [ 47 ] over 7 upon admission and Boari [ 48 ] over 8, but the first and last authors did not specify which Brixia score they used: A, H or E. Similarly, Hoang [ 49 ] and Gurtoo [ 50 ] also correlated Brixia score with the outcomes in COVID-19 patients but did not specify which Brixia score they used in calculations—either A, H or E score—or if there was more than one chest X-ray taken of each patient. In another study, Boari [ 51 ] even correlated the Brixia score with the lung involvement at the posthospitalization follow-up.…”
Section: Discussionmentioning
confidence: 99%